Internet design concepts and network 5.0 technologies - Lintao JIANG; Xiuying NIE; Jie ZHANG (Dianxin kexue)
The internet has been developed for more than 50 years, but its design concept has never changed.The business network is completely OTT, IP network is still “best effort”, which restricts the development of the internet.In order to continuously meet the needs of social development, the internet design idea needs to be changed, and the feasible direction is to be from “application-centered” to the “network-centered”.Network 5.0 is the fifth generation of data network, compared with the fourth generation of data network (IP network), it retains all the advantages of IP network, filling the absence of IP network in network performance and ability, with qualitative progress in performance and ability.The key technical issues on scalability, endogenous credible security, certainty and more aspects of network 5.0 were specifically discussed.